Effect of protease supplementation on the performance of laying chickens fed low protein diets in early production cycle (2013)
A 10 week study w as conducted to investigate the effect of diets supplemented with protease on .he performance of 32 weeks old Isa Brow n hens housed in cages and fed low Crude Protein (CP) diets in a completely randomized design. A total of 60 Isa Brown laying birds were randomly allotted to 5 dietary treatments each having six replicates of 2 birds per replicate. The diets were formulated to contain 16% crude protein (Treatment 1) which was the control diet: T2. 15.2% CP diet (5% CP reduction): T3. I5.20% CP diet + 0.05% protease: T4. 14.4% CP diet (10% CP reduction) and T5. 14.4% CP diet 0.05% protease. Feed and water were supplied ad libitum. Results showed that feed intake, Haugh unit and hen day production were not significant (p > 0.05). Addition of enzyme to 15.2 and 14.4% CP diets improved egg weight, shell weight, shell thickness and albumen weight. Yolk weight was improved by 14.4% CP diet. In conclusion, 10% CP reduction plus protease gave optimum performance of the laying hens and could be adopted.